2007
DOI: 10.1002/ejoc.200700086
|View full text |Cite
|
Sign up to set email alerts
|

New Amino Endoperoxides Belonging to the Antimalarial G‐Factor Series

Abstract: In the search for new antimalarial endoperoxides we developed a direct route for the preparation of new amino compounds belonging to the G-factor series. During the synthesis, a significant difference in reactivity between two series of diastereoisomers was observed. The final amino endoperoxides were obtained with 58 to 70 % yields, depending on the starting amine, in the "anti" series, but with the "syn" diastereoisomers an unexpected rearrangement occurred during the deprotection step. This was attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Compounds with high antimalarial [ 11 23 ], antihelminthic [ 24 28 ], and antitumor activities [ 29 34 ] were found among natural, semisynthetic, and synthetic peroxides. The main biologically active frame of these compounds includes five-membered 1,2-dioxolane [ 35 37 ], 1,2,4-trioxolane [ 38 39 ], and six-membered 1,2-dioxane [ 40 42 ], 1,2-dioxene [ 43 ], 1,2,4-trioxane [ 22 , 44 45 ] cycles. The naturally occuring peroxide artemisinin and its semisynthetic derivatives, artemether, arteether, and artesunate, are applied in large scale for malaria treatment [ 46 – 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds with high antimalarial [ 11 23 ], antihelminthic [ 24 28 ], and antitumor activities [ 29 34 ] were found among natural, semisynthetic, and synthetic peroxides. The main biologically active frame of these compounds includes five-membered 1,2-dioxolane [ 35 37 ], 1,2,4-trioxolane [ 38 39 ], and six-membered 1,2-dioxane [ 40 42 ], 1,2-dioxene [ 43 ], 1,2,4-trioxane [ 22 , 44 45 ] cycles. The naturally occuring peroxide artemisinin and its semisynthetic derivatives, artemether, arteether, and artesunate, are applied in large scale for malaria treatment [ 46 – 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of aldehydes (R 1 R 2 CHCHO) with R 1 or R 2 bearing a hydroxyl group (R 1 or R 2 equals to CH 2 OH or CH 2 CH 2 OH, and CH 3 ) allows the obtention of endoperoxides with a functionalized lateral chain which are presented in Table 2 together with their antiplasmodial activities. In all cases, this hydroxyl group was protected as a tert-butyldiphenyl silyl (TBDPS) [51,61] or a paramethoxybenzyl (PMB) group. [62] Methylation of the peroxyhemiketal moiety, cleavage of the protective group, and terminal hydroxyl transformation afforded mono and difluoro-endoperoxides 25, 26 with interesting antiplasmodial activities (lower than 1 .…”
Section: Modifications On the Lateral Chainmentioning
confidence: 99%
“…In the course of the large-scale search for synthetically accessible and cheap antimalarial peroxides (compared with natural and semi-synthetic structures), it was found that structures containing 1,2-dioxolane [ 88 90 ], 1,2,4-trioxolane [ 91 – 101 ], 1,2-dioxane [ 102 – 112 ], 1,2-dioxene [ 113 119 ], 1,2,4-trioxane [ 120 127 ] or 1,2,4,5-tetraoxane rings [ 128 146 ] exhibit pronounced activity, and in some cases, even superior to that of artemisinin.…”
Section: Introductionmentioning
confidence: 99%